Hemispherical and aspheric wgm dielectric resonators with conducting endplates: radiation and conductivity losses depending on shape of the resonators surface - Barannik, A.A.; Cherpak, N.T.; Kharchenko, M.S.; Vitusevich, S.A. (Радіофізика та електроніка, 2013)
The aim of the work is to study the radiation and conductivity losses in whispering gallery mode (WGM) resonators of different shape of the body of rotation. In this work, electromagnetic properties of a number of WGM resonators with conducting endplates are studied. Losses are studied in Ka-band for two kinds of dielectric material, namely, isotropic (Teflon) and anisotropic (single-crystal sapphire). For the Teflon hemispherical resonator, the analytical approach is used and its results are compared with the results of experimental measurements. The resonators of other shapes are studied experimentally. Experiments show that aspheric sapphire resonator has maximum coefficient As. however the radiation Q-factor is larger in the hybrid sapphire resonator (aspheric+cylindrical disk). Thus, the hybrid resonator with As 25 % greater than As of the hemispherical resonator with approximately the same radiation loss is a better option for the (super)conductor measurement purpose in microwave range. Метою роботи є дослідження радіаційних втрат і втрат, зумовлених провідністю в резонаторах різної форми обертання з хвилями шепочучої галереї (ШГ). У роботі досліджуються електромагнітні властивості ряду резонаторів з хвилями ШГ з торцевими провідними стінками. Втрати вивчаються в Kа-діапазоні для двох видів діелектричного матеріалу, а саме ізотропного (тефлон) і анізотропного (монокристалічний сапфір). Для тефлонового напівсферичного резонатора використовується аналітичний підхід, і його результати порівнюються з результатами експериментальних вимірювань. Результати для інших форм досліджуються експериментально. Експерименти показують, що асферичний сапфіровий резонатор має найбільший коефіцієнт As, проте радіаційна добротність вища для гібридного сапфірового резонатора (асферичний+циліндричний диск). Таким чином, гібридний резонатор з As на 25 % вищим, ніж As напівсферичного резонатора з приблизно тими ж радіаційними втратами, є кращим вибором для вимірювань властивостей (над) провідників в мікрохвильовому діапазоні. Целью работы является исследование радиационных потерь и потерь, обусловленных проводимостью в резонаторах различной формы вращения с волнами ШГ. В работе изучаются электромагнитные свойства ряда резонаторов с волнами шепчущей галереи (ШГ) с торцевыми проводящими стенками. Потери изучаются в Kа-диапазоне для двух видов диэлектрического материала, а именно изотропного (тефлон) и анизотропного (монокристаллический сапфир). Для тефлонового полусферического резонатора используется аналитический подход, и его результаты сравниваются с результатами экспериментальных измерений. Результаты для других форм исследуются экспериментально. Эксперименты показывают, что асферический сапфировый резонатор имеет наибольший коэффициент As, однако радиационная добротность выше для гибридного сапфирового резонатора (асферический+цилиндрический диск). Таким образом, гибридный резонатор с As на 25 % более высоким, чем As полусферического резонатора с примерно теми же радиационными потерями, является лучшим выбором для измерений свойств (сверх) проводников в микроволновом диапазоне.